Pemberdayaan Masyarakat Pesisir Pada Program Gerbang Mapan di Desa Ketapang oleh Pemerintahan Kabupaten Tangerang - Mayrudin, Yeby Ma'asan; Royadi, Irma Novia (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2024)
This article describes the realization of community empowerment policies in the Gerbang Mapan Program in Ketapang Village by the Tangerang Regency government. Ketapang Village is the focus of empowerment through a program, namely ”Gerbang Mapan” (Gerakan Pembangunan Masyarakat Pantai with various coaching and training activities for the community. Community empowerment is considered effective in advancing the community in Ketapang Village. We use the theory of community empowerment formulated by Sunyoto Usman as an analytical tool. The research method used is qualitative with a case study approach by deepening community empowerment in the form of activities in the form of empowering MSMEs through training and coaching and developing mangrove ecotourism. The results of the study showed that the community empowerment program in Ketapang Village was partially successful in empowering the community to become an independent and empowered community. However, there are challenges in implementing this Gerbang Mapan program, namely the lack of Mangrove tourism visitors has an impact on the low sales results of MSMEs of community business actors.